Ethno-Learning and Character Formation: Values and Morals through Culture-Based Education in Cirebon - Ade Cahyaningsih; Encep Syarief Nurdin; Dasim Budimansyah; Yadi Ruyadi; Jagad Aditya Dewantara (Jurnal Moral Kemasyarakatan, 2025)
This study explores how formal education preserves local culture through an ethno-learning approach in government-based schools in Cirebon, Indonesia. Using a multisite ethnographic method, the research was conducted over one year in four secondary schools known for integrating Cirebonese cultural values into teaching. The integration of local culture such as tari topeng (mask dance), gamelan, the Cirebonese language, and the Jelajah Budaya (Cultural Exploration) program helps strengthen students’ cultural identity, develop moral character, and foster positive social dispositions. Teachers act as cultural mediators, connecting tradition with contemporary education. Student engagement varies depending on family background and cultural exposure outside school. Challenges include limited resources, inconsistent student interest, and the need for more adaptive, student-centered pedagogies. The study highlights that culture-based education is not merely supplementary but foundational in forming character, reinforcing identity, and promoting cultural sustainability. It argues for a more contextual, humanistic model of education that aligns with local realities while addressing global educational demands.